2021
DOI: 10.1007/s40031-021-00652-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss and Efficiency Analysis of BLDC Motor and Universal Motor by Mathematical Modelling in the Mixer Grinder

Abstract: The typical mixer grinders are universal motor, which operates on alternating current supply because of the higher starting torque characteristics and easy speed control. The absence of brushes in the Brushless DC (BLDC) motor and noise reduction improves its life and makes it perfectly suited for mixer grinder. The mathematical modelling and experimental demonstration of a conventional universal motor and proposed simulated model of BLDC motor was analysed using the MATLAB/Simulink. The loss and efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several studies have improved the performance of universal motors, as reported in the literature in recent years. The author used Simulink to compare the functionality of BLDC motor drives and universal motors for mixers and grinders [11]. The author demonstrated how the universal motor behaves when operating on an AC and DC supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have improved the performance of universal motors, as reported in the literature in recent years. The author used Simulink to compare the functionality of BLDC motor drives and universal motors for mixers and grinders [11]. The author demonstrated how the universal motor behaves when operating on an AC and DC supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Where kh is the material hysteresis constant, B is the flux density maximum, n is the exponent of materialdependent, f is the frequency, m is the mass, A area of core, P is number of poles, N is speed, and 𝜙 is flux around the air gap. The eddy-current loss can be determined by (10) and (11).…”
Section: Core Lossesmentioning
confidence: 99%
“…The author economically designed motor for feasible applications using rotor ends by changing the magnetic flux density and material, to determine eddy current and loss analysis, there is enhancement in performance [6]- [9]. The author compared the performance of universal motor and BLDC motor drive using simulink for the grinder and mixer [10]. The author presented the behavior scanning of the  ISSN: 2302-9285 universal motor works on the AC and DC supply, which was achieved with MATLAB Simulink's help to know the motor's better performance on which supply results that motor performs better on DC supply [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nayak and Shivarudraswamy [17] presented a model of a brushless direct current (BLDC) motor and universal motor for grinder mixer application. The authors only concentrated on the electrical analysis part of the motors and did not consider the crucial parameter of magnetic analysis.…”
Section: Literature Reviewmentioning
confidence: 99%